Economic assessment of chemical looping oxygen production and chemical looping combustion in integrated gasification combined cycles. (November 2018) - Cloete, Schalk; Tobiesen, Andrew; Morud, John; Romano, Matteo; Chiesa, Paolo; Giuffrida, Antonio; Larring, Yngve
Highlights: Economic assessments of several IGCC-based CCS plants are presented. Introduction of CLC technology reduces CO2 avoidance costs by €11/ton. Replacing the ASU with novel CLOP reactors only reduce costs by €1/ton. Including hot gas clean-up technology reduces costs by a further €9/ton. The best performing plant is competitive with other low-carbon energy technologies. Abstract: Chemical looping promises significant reductions in the cost of CO2 capture and storage (CCS) by enabling energy conversion with inherent separation of CO2 at almost no energy penalty. This study evaluates the economic performance of a novel power plant configuration based on the principle of packed bed chemical looping. The new configuration, called COMPOSITE, integrates packed bed chemical looping combustion (PBCLC) and chemical looping oxygen production (CLOP) into an integrated gasification combined cycle (IGCC) power plant. The CLOP unit achieves air separation with minimal energy penalty and the PBCLC unit achieves fuel combustion with inherent CO2 capture. The COMPOSITE configuration achieved a competitive CO2 avoidance cost (CAC) of €45.8/ton relative to conventional IGCC with pre-combustion CO2 capture with €58.4/ton. However, the improvement was minimal relative to a simpler configuration using an air separation unit (ASU) instead of the CLOP reactors, returning a CAC of €47.3/ton. The inclusion of hot gas clean-up further improved the CAC of the COMPOSITE configuration to €37.8/ton. Optimistic technology assumptions in the form of lower contingency costs and better CLOP reactor performance reduced the CAC to only €24.9/ton. Further analysis showed that these highly efficient chemical looping plants will be competitive with other low-carbon power plants (nuclear, wind and solar) in a technology-neutral climate policy framework consistent with a 2 °C global temperature rise. Economic attractiveness improves further in a high CO2 tax scenario where large-scale deployment of CO2 negative bio-CCS plants is required.